Agama Kristian Kini dan Pengasasnya - Daud, Zakaria @ Mahmod (Jurnal Usuluddin, 1996)
This article explains that today's christianity is not a samawi religion anymore. It is because it's rules have been changed and amended to form as a universal relegion. Therefore, this article describes the new founder and his new teachings in today's Christianity which are contradict with Islamic's teaching.